ION-INDUCED ELECTRON EMISSION FROM THE CARBON TARGETS - Qayyum, A.; Ahmad, W.; Mahmood, M. I. (The Nucleus, 2020)
We describe characteristics and operation of a secondary electron detector geometry, which is recently developed for measuring the ion-induced total electron emission yield, ï§, and kinetic energy distribution of electrons released from solid targets. This setup has been successfully applied to measure Î³ of a carbon target bombarded with 1-10 keV singly charged ions Ne+ and Ar+. It was observed that in investigated energy range ï§ increases with the ion energy and mass. Moreover, the expected proportionality between ï§ and electronic stopping power was found. The detector geometry is relatively simple and is suitable for measurements over wide range of ion energies and target materials. PACS: 34.50.Dy; 79.20. Rf